Beating the odds (2): a new index of intergenerational social mobility - Jonathan Gershuny (University of Essex, Institute for Social and Economic Research (ISER), 2002)
The twin starting points for this paper are recent discussions in economic theory concerning the normative foundations for indices of intergenerational mobility, and the development of a human capital score intended (in conjunction with a parallel measure of individual wealth) to act as an indicator of social class. The paper specifies an intergenerational Gini-type mobility index, based on the mean expected earnings of the children of fathers in each class. It makes a series of estimates of mobility in Britain from BHPS lifetime employment history files. The first of these uses the Goldthorpe three-category class schema for both origins and destinations; the resulting estimates suffer from (1) the systematic exclusion of those (particularly women) outside employment, and (2) the effects of the changes in the sizes of the class categories. The second estimation is a hybrid using Goldthorpe (seven category) origins and human capital quintile destination categories; this deals with problem (1) but not problem (2), The third estimation uses human capital quintiles for both origin and destination categories, and avoids both problems. But it is dominated by the fourth approach, a continuous version of the Gini index using scalar variables (the fathers human capital scores and the childrens expected earnings). The womens intergenerational Gini score now shows substantial increases from the 1935-44 birth cohort to the 1955-64 birth cohort; the mens score shows small increases over the same period. The conclusion is that in terms of this index, intergenerational mobility in Britain has become more unequal overall.
Keywords: 330